2012
DOI: 10.2500/ajra.2012.26.3720
|View full text |Cite
|
Sign up to set email alerts
|

Orally Exhaled Nitric Oxide in Patients with Seasonal Allergic Rhinitis during Natural Pollen Season

Abstract: Natural exposure may lead to an elevation of ENO in the patients with SAR without asthma. We estimate that the increased ENO may result from subclinical allergic inflammation present within the lower airways of nonasthmatic patients with SAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Exhaled breath from patients with allergic rhinitis or asthma has been shown to contain higher NO ˙ levels compared to healthy controls. Exhaled NO ˙ was demonstrated to be significantly elevated in allergic rhinitis during the nonpollen season, whilst others reported a further increase in the pollen season [73, 74]. Plasma NO ˙ metabolite levels could not be related to asthma, allergic sensitization or allergic rhinitis disease phenotypes in a study involving 523 individuals [75].…”
Section: No˙ In Allergymentioning
confidence: 99%
“…Exhaled breath from patients with allergic rhinitis or asthma has been shown to contain higher NO ˙ levels compared to healthy controls. Exhaled NO ˙ was demonstrated to be significantly elevated in allergic rhinitis during the nonpollen season, whilst others reported a further increase in the pollen season [73, 74]. Plasma NO ˙ metabolite levels could not be related to asthma, allergic sensitization or allergic rhinitis disease phenotypes in a study involving 523 individuals [75].…”
Section: No˙ In Allergymentioning
confidence: 99%
“…Although patients in the present study were diagnosed without asthma, most of them in both treatment groups had increased fractional NO at baseline, possibly indicating presence of subclinical allergic inflammation within the lower airways, as indicated by Ciebiada and colleagues. 34 Although there was no difference in the number of participants with FeNO ≥30 ppb between the two treatment groups at baseline, treatment for 14 days with BD + MNT significantly reduced the number of participants with FeNO ≥30 ppb by 50%, whereas it was not significantly altered by BD alone. Furthermore, the finding from the present study that BD + MNT was significantly more effective than BD in reducing the FeNO concentrations suggests a protective effect of MNT against lower airway inflammation.…”
Section: Discussionmentioning
confidence: 86%
“…Exhaled nitric oxide (eNO) is an easily measurable endogenous molecule, which is usually assessed as a noninvasive marker in asthma, including milder stages of the disease. 25,33 A study by Ciebiada and colleagues 34 has demonstrated that eNO is also increased in AR patients without asthma, especially during the pollen season, suggesting that subclinical allergic inflammation may be present within the lower airways of nonasthmatic patients with SAR. Although patients in the present study were diagnosed without asthma, most of them in both treatment groups had increased fractional NO at baseline, possibly indicating presence of subclinical allergic inflammation within the lower airways, as indicated by Ciebiada and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…At the forefront is the unified airway hypothesis, which states that both upper and lower airway allergic symptoms are manifestations of the same atopic disease [11]. Asthma and rhinitis share many pathophysiologic characteristics [12] and studies suggest that subclinical allergic inflammation is present in the lower airway of patients with allergic rhinitis [13]. Clinically, both allergic rhinitis and asthma are triggered by many of the same environmental allergens [14].…”
Section: Introductionmentioning
confidence: 99%